2010
DOI: 10.1523/jneurosci.5657-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Form of Prion Protein Inhibits Reelin-Mediated Shedding of Caspr from the Neuronal Cell Surface to Potentiate Caspr-Mediated Inhibition of Neurite Outgrowth

Abstract: Extension of axonal and dendritic processes in the CNS is tightly regulated by outgrowth-promoting and -inhibitory cues to assure precision of synaptic connections. We identify a novel role for contactin-associated protein (Caspr) as an inhibitory cue that reduces neurite outgrowth from CNS neurons. We show that proteolysis of Caspr at the cell surface is regulated by the cellular form of prion protein (PrP), which directly binds to Caspr. PrP inhibits Reelin-mediated shedding of Caspr from the cell surface, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 62 publications
0
45
2
Order By: Relevance
“…Experiments in mice lacking Caspr showed that it is required in the formation of paranodal junctions that are important for saltatory conduction (63). Caspr is newly reported to be involved in inhibition of neurite outgrowth in CNS neurons (64). Regarding the potential association of Caspr to AD, the CSF and plasma levels of CNTNAP1 and/or CNTN (CNTN1 and/or -2) are altered in AD individuals, and it is possible that these changes could be used for diagnosis of AD (65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in mice lacking Caspr showed that it is required in the formation of paranodal junctions that are important for saltatory conduction (63). Caspr is newly reported to be involved in inhibition of neurite outgrowth in CNS neurons (64). Regarding the potential association of Caspr to AD, the CSF and plasma levels of CNTNAP1 and/or CNTN (CNTN1 and/or -2) are altered in AD individuals, and it is possible that these changes could be used for diagnosis of AD (65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were washed twice with ice-cold PBS. Surface proteins were then biotinylated with 0.5 mg/ml of EZ-Link Sulfo-NHS-LC-Biotin (Pierce) applied for 30 min at 4°C (20). The reactions were stopped by adding 50 mM glycine for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Open-field locomotion was assessed by a mouse rating scale, the Basso Mouse Scale (BMS; Basso et al, 2006). In addition, motor performance was examined using videobased single-frame motion analysis, an established approach for the evaluation of motor recovery after spinal cord lesions in mice (Apostolova et al, 2006;Chen et al, 2007Chen et al, ,2010Cui et al, 2011;Devanathan et al, 2010;Jakovcevski et al, 2007;Lee et al, 2009;Mehanna et al, 2010;Semler et al, 2011;Xu et al, 2011). Motor behavior of individual animals was recorded while the mice were performing two tasks: the beamwalking test and the pencil-grabbing test.…”
Section: Analyses Of Motor Functionmentioning
confidence: 99%